Radiation-Induced Transformation of Immunoregulatory Networks in the Tumor Stroma - Martinez-Zubiaurre, Inigo; Chalmers, Anthony J.; Hellevik, Turid (Frontiers in Immunology, 2018)
The implementation of novel cancer immunotherapies in the form of immune checkpoint blockers represents a major advancement in the treatment of cancer, and has renewed enthusiasm for identifying new ways to induce antitumor immune responses in patients. Despite the proven efficacy of neutralizing antibodies that target immune checkpoints in some refractory cancers, many patients do not experience therapeutic benefit, possibly owing to a lack of antitumor immune recognition, or to the presence of dominant immunosuppressive mechanisms in the tumor microenvironment (TME). Recent developments in this field have revealed that local radiotherapy (RT) can transform tumors into in situ vaccines, and may help to overcome some of the barriers to tumor-specific immune rejection. RT has the potential to ignite tumor immune recognition by generating immunogenic signals and releasing neoantigens, but the multiple immunosuppressive forces in the TME continue to represent important barriers to successful tumor rejection. In this article, we review the radiation-induced changes in the stromal compartments of tumors that could have an impact on tumor immune attack. Since different RT regimens are known to mediate strikingly different effects on the multifarious elements of the tumor stroma, special emphasis is given to different RT schedules, and the time after treatment at which the effects are measured. A better understanding of TME remodeling following specific RT regimens and the window of opportunity offered by RT will enable optimization of the design of novel treatment combinations.